Shedding light on light photographic lighting explained. (White Plains, N.Y. Center for Humanities, 1978)
Explores twelve dimensions or subtleties of light which are important in photography. These include source, direction, key sharpness, color, texture, reflection, polished objects, experimental directions, underwater, atmosphere, and time.
Keywords: Photography -- Lighting; Arts; Art studies